A Novel Ex Vivo Model of Aortic Valve Calcification. A Preliminary Report - Zabirnyk, Arsenii; Perez, Maria del Mar; Blasco, Marc; Stensløkken, Kåre-Olav; Ferrer, Miguel D.; Salcedo, Carolina; Vaage, Jarle (Frontiers in Pharmacology, 2020)
Background: No pharmacological treatment exists to prevent or stop the calcification process of aortic valves causing aortic stenosis. The aim of this study was to develop a robust model of induced calcification in whole aortic valve leaflets which could be suitable for studies of the basic mechanisms and for testing potentially inhibitory drugs. Methods: Pig hearts were obtained from a commercial abattoir. The aortic valve leaflets were dissected free and randomized between experimental groups. Whole leaflets were cultured in individual wells. Two growth media were used for cultivation: standard growth medium and an antimyofibroblastic growth medium. The latter was employed to inhibit contraction of the leaflet into a ball-like structure. Calcification was induced in the growth medium by supplementation with an osteogenic medium. Leaflets were cultivated for four weeks and medium was changed every third day. To block calcification, the inhibitor SNF472 (a formulation of the hexasodium salt of myo-inositol hexaphosphate) was used at concentrations between 1 and 100 µM. After cultivation for four weeks the leaflets were snap frozen in liquid nitrogen and kept at -80°C until blind assessment of the calcium amount in leaflets by inductively coupled plasma optical emission spectroscopy. For statistical analysis, a Kruskal–Wallis test with Dunn's post-test was applied. Results: Osteodifferentiation with calcium accumulation was in principle absent when standard medium was used. However, when the antimyofibroblastic medium was used, a strong calcium accumulation was induced (p=0.006 compared to controls), and this was blocked in a dose-dependent manner by the calcification inhibitor SNF472 (p=0.008), with an EC50 of 3.3 µM. Conclusion: A model of experimentally induced calcification in cultured whole leaflets from porcine aortic valves was developed. This model can be useful for studying the basic mechanisms of valve calcification and to test pharmacological approaches to inhibit calcification.